Morphological, biochemical, and molecular characterization of potential plant growth-promoting rhizobacterial strains from metroxylon sagu rottb. (SAGO) palms - Nemenzo, Phoebe S. (Institute of Biology, College of Science, University of the Philippines Diliman, 2010)
Three bacterial strains isolated from the rhizosphere of metroxylon sagu rottb. (sago) palms in Agusan Marsh, Mindanao were previously observed to have potential plant growth-promoting properties, i.e. increasing the radicle length in corn varieties, viz., NK 5447 Bt and NK 5447 conventional, and increasing the shoot length in tomato varieties, viz., Improved Pope and diamante. Antifumgal properties of the three strains against penicillium sp. and curvularia sp. were also reported to be observed in the same tomato varieties. This study was mainly directed at establishing the taxonomic identity of these three rhizobacterial strains which were previously reported to exhibit plant growth-promoting properties on metroxylon sagu suckers. The three strains were characterized by examining their cell and colony morphology, biochemical, and molecular characteristics. The three rhizobacterial strains appeared rod-shaped with rounded ends, irregularly occurring in singles, pairs, or clusters. This study is deemed useful for the development of a biofertilizer from one or a combination of any of these three rhizobacteria and enhancement in the cultivation of M. sagu palms and other plant species. Further, the development of biofertilizers from these rhizobacteria will contribute to the promotion of "greener technologies".